Antioxidant Films Based on Cross-Linked Methyl Cellulose and Native Chilean Berry for Food Packaging Applications - Guarda-Moraga, A; Rodriguez-Mercado, F; Galotto-Lopez, M; Lopez de Dicastillo-Bergamo, A (Elsevier Ltd, 2016)
Development of antioxidant and antimicrobial active food packaging materials based on biodegradable polymer and natural plant extracts has numerous advantages as reduction of synthetic additives into the food, reduction of plastic waste, and food protection against microorganisms and oxidation reactions. In this way, active films based on methylcellulose (MC) and maqui (Aristotelia chilensis) berry fruit extract, as a source of antioxidants agents, were studied. On the other hand, due to the high water affinity of MC, this polymer was firstly cross-linked with glutaraldehyde (GA) at different concentrations. The results showed that the addition of GA decreased water solubility, swelling, water vapor permeability of MC films, and the release of antioxidant substances from the active materials increased with the concentration of GA. Natural extract and active cross-linked films were characterized in order to obtain the optimal formulation with the highest antioxidant activity and the best physical properties for latter active food packaging application. © 2015 Elsevier Ltd.